2018
DOI: 10.1126/science.aar4983
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of feeding by somatostatin neurons in the tuberal nucleus

Abstract: The tuberal nucleus (TN) is a surprisingly understudied brain region. We found that somatostatin (SST) neurons in the TN, which is known to exhibit pathological or cytological changes in human neurodegenerative diseases, play a crucial role in regulating feeding in mice. GABAergic tuberal SST (SST) neurons were activated by hunger and by the hunger hormone, ghrelin. Activation of SST neurons promoted feeding, whereas inhibition reduced it via projections to the paraventricular nucleus and bed nucleus of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 35 publications
9
99
0
3
Order By: Relevance
“…Thus the uridine and uridine nucleotides may be novel regulators of body metabolism and function of AgRP/NPY neurons. In addition to AgRP/NpY neurons, ghrelin promotes activation of somatostatin neurons in the hypothalamic tuberal nucleus to promote feeding by inhibiting downstream neurons in the PVN and to the BNST (Luo et al 2018).…”
Section: Signaling In Agrp/npy Neuronsmentioning
confidence: 99%
“…Thus the uridine and uridine nucleotides may be novel regulators of body metabolism and function of AgRP/NPY neurons. In addition to AgRP/NpY neurons, ghrelin promotes activation of somatostatin neurons in the hypothalamic tuberal nucleus to promote feeding by inhibiting downstream neurons in the PVN and to the BNST (Luo et al 2018).…”
Section: Signaling In Agrp/npy Neuronsmentioning
confidence: 99%
“…There may be other neuronostatin neurons in the central nervous system that we could not identify using this technique. A recent report showed that the somatostatin neurons localized in the tuberal nucleus regulated feeding [39], suggesting that these neurons could co-express neuronostatin. However, with immunohistochemistry, we, and others [2], could not detect neuronostatin immunoreactivity in the tuberal nucleus.…”
Section: Physiological Stimulation Of Neuronostatin Neurons and Invesmentioning
confidence: 99%
“…Collateralization could, in principle, impose temporal synchrony on targets of VMHvl Esr1 neurons and coordinate their activity. Given this collateralization, assigning specific functions to individual projections (e.g., by optogenetic terminal stimulation, (22,57) will be technically challenging, due to back-propagation and collateral redistribution of action potentials from optogenetically stimulated terminals.…”
Section: Vmhvl Esr1 Neurons Collateralize Broadly Yet Specificallymentioning
confidence: 99%